The choice to report cycling crashes in Denmark: The role of attitudes, norms and perceived difficulty - Janstrup, Kira H.; Kaplan, Sigal; Prato, Carlo G. (Proceedings from the Annual Transport Conference at Aalborg University, 2015)
This study explores the behavioral factors underlying the reporting intentions of cycling accidents. The proposed analytical framework is an adapted version of the Theory of Planned Behavior (TPB), accounting for the linkage between attitudes and the perceived difficulties, in order to understand the barriers impeding cycling accident reporting intentions. The barriers consist of attitudes that accident reporting is useless, preference to allocate time to other activities, concerns about family distress and social image, distrust in the police, and medical consultation aversion. The framework was validated by means of a survey, which yielded 1,512 complete responses from cyclists. The estimated structural equation models revealed: (i) the perceived difficulties are related to reporting intentions, to attitudes that accident reporting is useless, and to the reference to allocate time to other activities; (ii) medical consultation aversion has a higher weight than distrust in the police in demotivating cycling accident reporting intentions; (iii) the latent factors are mainly related to the socio-economic characteristics and the characteristics of the last cycling accident; (iv) information provision regarding the societal benefits of accident reporting is important for increasing the reporting rate.